An Analysis on Directive Speech Act Found in Jumanji: The Next Level Movie Directed by Jake Kashan - Agung Trihanto (Universitas Veteran Bangun Nusantara, 2022)
Directive speech acts are words to order someone so the other people take action according to the request of the speaker both directly and indirectly. This study discusses about An Analysis of Directive Speech Acts Found in Jumanji: The Next Level Movie Directed by Jake Kashan. The purpose of this study is to identify the kinds and the forms of directive speech acts found in Jumanji: The Next Level movie directed by Jake Kashan. This research was conducted using qualitative method. The main instrument of this research is the researcher himself. The researcher as a human instrument used laptop, movie, note book, pen, dictionary as the supporting instrument. The data of this research was collected by documentation and content analysis. The result of the analysis showed 6 types of directive speech acts found in Jumanji: The Next Level Movie Directed by Jake Kashan. They were: 3 data belonging to begging, 49 data belonging to commanding, 6 data belonging to forbidding, 1 data belonging to ordering, 5 data belonging to requesting, 6 data belonging to suggestions. The amount totals of data are 70. The forms of directive speech acts found in The Jumanji: The Next Level Movie Directed by Jake Kashan were declarative, imperative, and interrogative. 11 data belonging to declarative, 54 data belonging to imperative, and 4 data belonging to interrogative.